2020
DOI: 10.3389/fpsyg.2020.00816
|View full text |Cite
|
Sign up to set email alerts
|

Totality of the Evidence Suggests Prenatal Cannabis Exposure Does Not Lead to Cognitive Impairments: A Systematic and Critical Review

Abstract: Background: Despite limited data demonstrating pronounced negative effects of prenatal cannabis exposure, popular opinion and public policies still reflect the belief that cannabis is fetotoxic. Methods:This article provides a critical review of results from longitudinal studies examining the impact of prenatal cannabis exposure on multiple domains of cognitive functioning in individuals aged 0 to 22 years. A literature search was conducted through PsycINFO, PubMed, and Google Scholar. Articles were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 63 publications
0
25
0
1
Order By: Relevance
“…However, most performance effects from these cohorts were relatively subtle, and inconsistencies were present. Indeed, a recent systematic review of these data and other smaller cohorts determined that outcomes differed on only 4.3% of cognitive measures (with cannabis exposure being associated with worse outcomes in 3.4% of cognitive measures) ( 84 ). This review also concluded that the statistical differences were not clinically significant.…”
Section: Neurodevelopmental Outcomes Of Prenatal Cannabinoid Exposurementioning
confidence: 99%
“…However, most performance effects from these cohorts were relatively subtle, and inconsistencies were present. Indeed, a recent systematic review of these data and other smaller cohorts determined that outcomes differed on only 4.3% of cognitive measures (with cannabis exposure being associated with worse outcomes in 3.4% of cognitive measures) ( 84 ). This review also concluded that the statistical differences were not clinically significant.…”
Section: Neurodevelopmental Outcomes Of Prenatal Cannabinoid Exposurementioning
confidence: 99%
“…11:816. doi: 10.3389/fpsyg.2020.00816 Recent legalization of cannabis use in 40 American states and all Canadian provinces and territories has created an urgent need for evidence surrounding the implications of in-utero cannabis exposure for infant and child health outcomes, including cognitive functioning. A recently published systematic review by Torres et al (2020) aimed to synthesize and critically appraise results from longitudinal studies examining the impact of prenatal cannabis exposure on multiple domains of cognitive functioning in individuals aged 0 to 22 years. The authors present a strong critical appraisal of the included literature and clearly highlight the limited evidence in this area.…”
Section: Totality Of the Evidence Suggests Prenatal Cannabis Exposurementioning
confidence: 99%
“…11:1891. doi: 10.3389/fpsyg.2020 We appreciate the expressed interest of Chaput et al (2020) in our recent critical review of the literature investigating the impact of prenatal cannabis exposure on subsequent cognitive functioning of offspring (Torres et al, 2020). We concluded that the available empirical "evidence does not suggest that prenatal cannabis exposure alone is associated with clinically significant cognitive functioning impairments."…”
Section: Commentary: Totality Of the Evidence Suggests Prenatal Cannamentioning
confidence: 99%